2019
DOI: 10.2147/cmar.s185232
|View full text |Cite
|
Sign up to set email alerts
|

<p>Natural gypenosides: targeting cancer through different molecular pathways</p>

Abstract: The second foremost cause of mortality around the word is cancer. Conventional therapies, such as radiation, surgery, and chemotherapy have limited accessibility owing to secondary resistance. Therefore, convenient, safe, and nonresistant drugs are urgently needed. Plant-derived natural products have attracted considerable interest owing to their high efficacy, low toxicity, and convenience. Gypenosides (Gyp) inhibit invasion, migration, metastasis, and proliferation and induce apoptosis in different cancers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 92 publications
(103 reference statements)
0
23
0
Order By: Relevance
“…Cancer is the second foremost cause of mortality in the world (Ahmad, Khan, et al, 2019). Conventional therapies including surgery, radiation, and chemotherapy have limited success due to secondary resistance (Ahmad, Khan, et al, 2019; Su et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cancer is the second foremost cause of mortality in the world (Ahmad, Khan, et al, 2019). Conventional therapies including surgery, radiation, and chemotherapy have limited success due to secondary resistance (Ahmad, Khan, et al, 2019; Su et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the second foremost cause of mortality in the world (Ahmad, Khan, et al, 2019). Conventional therapies including surgery, radiation, and chemotherapy have limited success due to secondary resistance (Ahmad, Khan, et al, 2019; Su et al, 2018). Therefore, safe, non‐resistant, less toxic, and convenient drugs are urgently required (Ahmad, Khan, et al, 2019; Su et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell cycle controls the cell growth, while its deregulation causes aberrant proliferation of the cells (Williams & Stoeber, ). It has been reported that the natural compounds are highly active (Ahmad et al, ; Pengyu, Ahmad, & Lijuan, ) and reverse proliferation through the arrest of the cell cycle (Bailon‐Moscoso, Cevallos‐Solorzano, Romero‐Benavides, & Orellana, ). Flow cytometry analysis showed that STM induced G2/M phase cell cycle arrest in L1210 cells (Ma et al, ) (Figure and Table ).…”
Section: Anticancermentioning
confidence: 99%